2021
DOI: 10.1016/j.omtm.2021.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Defining the optimal dose and therapeutic window in SMA with respiratory distress type I model mice, FVB/NJ-Ighmpb2

Abstract: Spinal muscular atrophy with respiratory distress type 1 (SMARD1) is an autosomal recessive disorder that develops in infancy and arises from mutation of the immunoglobulin helicase μ-binding protein 2 ( IGHMBP2 ) gene. Whereas IGHMBP2 is ubiquitously expressed, loss or reduction of function leads to alpha motor neuron loss and skeletal muscle atrophy. We previously developed a gene therapy strategy for SMARD1 using a single-stranded AAV9- IGHMBP2 vector and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In contrast, all atrophic disease patterns were comparable to the Nmd 2J mouse. In a subsequent study, Shababi et al then showed, very impressively, that at low and high doses, applications at an earlier time point (P2-3), as opposed to a later time point (P6-P8), had a significantly improved effect on survival, motor function, muscle pathology, gastrocnemius NMJ pathology, and spinal motoneuron numbers from L3 to L5 [65]. However, it must be acknowledged that the application of AAV9-IGHMBP2 at a later time point also leads to a significant improvement of the disease pattern, but not as significant as for P2-3 [65].…”
Section: Aav9-ighmbp2 Application To the Nmd 2j Modelmentioning
confidence: 99%
“…In contrast, all atrophic disease patterns were comparable to the Nmd 2J mouse. In a subsequent study, Shababi et al then showed, very impressively, that at low and high doses, applications at an earlier time point (P2-3), as opposed to a later time point (P6-P8), had a significantly improved effect on survival, motor function, muscle pathology, gastrocnemius NMJ pathology, and spinal motoneuron numbers from L3 to L5 [65]. However, it must be acknowledged that the application of AAV9-IGHMBP2 at a later time point also leads to a significant improvement of the disease pattern, but not as significant as for P2-3 [65].…”
Section: Aav9-ighmbp2 Application To the Nmd 2j Modelmentioning
confidence: 99%
“…We generated a FVB- Ighmbp2 +/nmd mouse that contains the same A-to-G mutation in intron 4 of Ighmbp2 . FVB- nmd lifespan is less variable (17–21 days) and while mutant mice initially gain weight, there is a rapid weight and motor function decline ( 32 , 33 ). FVB- nmd mutant mice demonstrate the same muscle weakness and hindlimb contractures as B6- nmd 2J mutant mice; however, disease pathology occurs earlier ( 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%